How are you, really? Let's talk - Tan, Yi Ting (Nanyang Technological University, 2024)
The intention with this final year project was to help me get a better understanding of the perspectives involved in mental health services in Singapore, especially from those who have used them. From there, I planned to identify the gaps in the system and accurately approach the problem through my design, be it in the form of a service, a spatial, interactive, digital, product design or an artistic approach.